Construction history : proceedings of the 6th International Congress on Construction History (6ICCH 2018), July 9-13, 2018, Brussels, Belgium /: proceedings of the 6th International Congress on Construction History (6ICCH 2018), July 9-13, 2018, Brussels, Belgium. (2018) - Unknown
No abstract available